Developing the notion of ubuntu as African theory for social work practice - Van Breda, Adrian (Social Work/Maatskaplike Werk, 2019)
<span style="font-family: ’Times New Roman’,’serif’; font-size: 14pt; mso-bidi-font-size: 12.0pt; mso-fareast-font-family: ’Times New Roman’; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-GB">Ubuntu is an African concept referring to humanness. It gives expression to deeply-held African ideals of one’s personhood being rooted in one’s interconnectedness with others. Social workers seeking to develop an African framework for decolonial social work practice turn repeatedly to ubuntu for aid. But the term has, for the most part, been limited to the idea of mutual aid – people helping each other in a spirit of solidarity. This article endeavours to extend and deepen the ubuntu concept to strengthen its potential as a theory informing social work practice. This is done by interweaving other African ideas with ubuntu in three domains: ethics, sustainable development and ecospirituality